IMPLEMENTASI TEKNOLOGI VOIP (Voice Over Internet Protocol) PADA JARINGAN PABX (Private Automatic Branch Exchange) DI LINGKUNGAN UNIVERSITAS WIDYAGAMA MALANG - Qustoniah, Anis; Siswanto, Diky (DINAMIKA DOTCOM, 2015)
VoIP is one part of the delivery method using the sound of a voice packet technique. VoIP will be used as an interface between the telephone with base intranet network Internet Protocol (IP). PABX equipment is very appropriate alternative when used in VoIP networks are connected in some conventional telephone. VoIP is cheap because users do not have to have a number of PSTN network so that the PABX is used as a means to know that VoIP can be used for voice connections directly on a PABX extension based on the numbering that has been determined by the PBX itself. Because simple and high economic value in communicating using this VoIP in this study will be implemented in the PABX network environment Widyagama University of Malang to suppress the cost / cost communications budget. In designing a VoIP network, which in the notice and analyzed is the problem of Quality of Service (QoS), delay and echo. VoIP system is similar to the existing PABX , the difference lies in his system , if the PABX using the analog system to a digital system because VoIP uses veifikasi required for synchronization between client and server . IP configuration adapted to the server where the server has been set with the IP address 192.168.2.110. Each communication device used in VoIP communications must be registered in the server which includes the configuration of VoIP numbers , IP server and password .From the test results showed that the delay, jitter and packet loss from the system built is still meet the standard ITU-T Y 1541. In terms of the cost, communication using VoIP to provide efficiency up to 50%.Keywords: Jaringan, VoIP, PABX